2021
DOI: 10.1021/acs.chemmater.1c02917
|View full text |Cite
|
Sign up to set email alerts
|

Michael Addition Reaction Assisted Derivation of Functional and Durable Superhydrophobic Interfaces

Abstract: Bioinspired superhydrophobicity embedded functional interfaces hold immense possibilities to remediate different existing challenges in our day to day life. However, the durability, scalability of the conventional biomimicked superhydrophobic interfaces, the lack of an avenue to embed different, relevant chemical functionalities to tailor the water wettability and other relevant physical properties are major concerns. In this perspective, we have provided an insight into the advantageous use of “reactive” chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19] Over the years, various research groups have developed biomimicked antiwetting interfaces ranging from a few nanometers thickness to bulk antiwetting materials for a wide range of applications in energy, healthcare, and environmental remediation. [21][22][23][24][25][26][27][28][29][58][59][60][61][62] Lithography, 63,64 plasma/chemical etching, 65,66 templation, 67,68 and electrospinning approaches 69,70 have often been adopted to construct different types of hierarchal topography, while various chemistries have been exploited to fulfil the low or high surface energy requirements. 6 There are numerous research articles and review papers that elaborate the aforementioned subjects.…”
Section: Bio-mimicked Antiwetting Interfaces: Weighing the Importance...mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17][18][19] Over the years, various research groups have developed biomimicked antiwetting interfaces ranging from a few nanometers thickness to bulk antiwetting materials for a wide range of applications in energy, healthcare, and environmental remediation. [21][22][23][24][25][26][27][28][29][58][59][60][61][62] Lithography, 63,64 plasma/chemical etching, 65,66 templation, 67,68 and electrospinning approaches 69,70 have often been adopted to construct different types of hierarchal topography, while various chemistries have been exploited to fulfil the low or high surface energy requirements. 6 There are numerous research articles and review papers that elaborate the aforementioned subjects.…”
Section: Bio-mimicked Antiwetting Interfaces: Weighing the Importance...mentioning
confidence: 99%
“…6 There are numerous research articles and review papers that elaborate the aforementioned subjects. [1][2][3][4][5][6][7][8][9][10][30][31][32][58][59][60][61][62] However, debate over the individual impact of topography and chemistry affecting the liquid repellence property has hardly been a matter of analysis in any review article. In the following sections, we aim to provide a detailed insight into how topography and chemistry play independently important roles in imparting and controlling different bio-inspired liquid wettability.…”
Section: Bio-mimicked Antiwetting Interfaces: Weighing the Importance...mentioning
confidence: 99%
“…The cross-sectional scanning electron microscopy (SEM) images revealed that the composite paper consisted of interlaced graphite nanoplates and softwood fibers. The lignin nanoparticles cover the surface of the paper forming a hierarchical microstructure, implying the hydrophobicity of the paper. …”
Section: Results and Discussionmentioning
confidence: 99%
“…Superhydrophobic modication could further improve the water stability of PeNCs. [122][123][124] For instance, Zhang et al developed a superhydrophobic lead PeNC lm by creating a self-assembled monolayer of 1H,1H,2H,2H-peruorodecanethiol. 36 The thiol group of the peruorocarbon chains passivated the uncoordinated sites on the perovskite surface by forming the Pb-S bond.…”
Section: Passivation By Post-treatment With a Hydrophobic/ Hydrophili...mentioning
confidence: 99%